The loss of Spinster homolog 2 drives endothelial mesenchymal transition via SMS2-mediated disruption of sphingomyelin metabolism: SPNS2 loss drives EndMT via SMS2 - Qin, Jin-feng; Li, Yuan; Wang, Xiao-dan; Tu, Shuangxi; Zhu, Xiao; Yin, Kai (Cellular and Molecular Biology, 2025)
Endothelial-mesenchymal transition (EndMT) is the process by which endothelial cells transform into mesenchymal cells, driving stromatogenesis and inflammatory responses, thereby contributing to the development of atherosclerotic plaques. Spinster homolog 2 (SPNS2), a protein responsible for S1P transport, regulates sphingolipid metabolism and signaling in endothelial cells to maintain vascular homeostasis. In the present work, we investigated the involvement of SPNS2 in endothelial mesenchymal transition. Knocking down SPNS2 in endothelial cells resulted in significant phenotypic changes, marked by a decrease in endothelial markers (CD31, VE-cadherin) and an increase in mesenchymal markers (Vimentin, α-SMA), confirming the occurrence of EndMT. Notably, SPNS2 knockdown leads to alterations in sphingolipid metabolism, most prominently marked by a significant increase in sphingomyelin (SM) levels. Similar cellular alterations were observed with the exogenous addition of SM, leading to the transition of endothelial cells from a cobblestone-like morphology to a dispersed, spindle-shaped form. In contrast, the exogenous addition of sphingomyelinase, which degrades SM, was able to reverse the endothelial-to-mesenchymal transition induced by SPNS2 knockdown. Mechanistically, our study suggests that SPNS2 knockdown promotes endothelial-to-mesenchymal transdifferentiation by upregulating SMS2 expression, which subsequently enhances sphingomyelin synthesis.